Efektivitas Booklet Terhadap Peningkatan Pelaksanaan Baby Gym - Tarigan, Eka Falentina; Sinaga, Siti Nurmawan; Nurhayati, Nurhayati (Midwifery Care Journal, 2023)
Impaired development and advancement was a issue that frequently found in society. There were numerous issues related with motoric advancement delays in Indonesia, indeed in spite of the fact that programs to progress the quality of children was one of the government's needs. In Indonesia, information from IDAI in 2017 on the rate of common formative delays was evaluated at 1-3% of children beneath 5 a long time of age encountering common formative delays. The reason of this study was to decide the viability of the booklet on the usage of the Child Exercise center at the Padang Bulan health center in Medan in 2022. This study was a quasi-experimental study with post test with control group. The booklet was a media in intervention group, the control group was not given a booklet. The mother and child went to the exercise center were 47 respondents. The Wilcoxon test was carried out, the comes about for P value were p = 0.000, demonstrating that there was a significant effect of booklet on child exercise center execution. It was recommended that the Head of the health center will execute the use of booklets within the Padang Bulan health center work region to stimulate development of baby.